2021
DOI: 10.1039/d0md00305k
|View full text |Cite
|
Sign up to set email alerts
|

A second generation of 1,2,4-oxadiazole derivatives with enhanced solubility for inhibition of 3-hydroxykynurenine transaminase (HKT) from Aedes aegypti

Abstract: Water-soluble oxadiazole-based HKT inhibitor library, comprising a new class of compounds for control of Aedes aegypti dissemination, act as competitive HKT enzyme inhibitors, promoting accumulation of the toxic metabolite 3-hydroxykynurenine in insect organism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…It also catalyzes the transamination of alanine with glyoxylate as an amino group acceptor, but less efficiently [ 10 , 13 ]. The detoxification function of the enzyme HKT over 3-HK makes HKT a potential insecticide target [ 14 , 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…It also catalyzes the transamination of alanine with glyoxylate as an amino group acceptor, but less efficiently [ 10 , 13 ]. The detoxification function of the enzyme HKT over 3-HK makes HKT a potential insecticide target [ 14 , 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…gambiae (AgHKT) . Previously, it was shown that AeHKT is inhibited by 1,2,4-oxadiazole derivatives with IC 50 values ranging from 35 to 340 μM via a noncompetitive mechanism. , In this work, we have investigated the binding free energies and dissociation kinetics of the complexes between the inhibitors 4-(2-aminophenyl)-4-oxobutyric acid (4OB) and sodium 4-(3-phenyl-1,2,4-oxadiazol-5-yl)­butanoate (OXA) and the enzymes AeHKT and AgHKT. We have found that OXA binds to both AeHKT and AgHKT enzymes with binding energies 2-fold more favorable than the crystallographic inhibitor 4OB.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, only 155 three-dimensional structures from mosquitoes were deposited in the Protein Data Bank until November 2022, attesting to the unexplored potential of insect proteins as drug targets for the control of vector-transmitted diseases. In this work, we solved the X-ray structure of AeHKT (PDB ID: 6MFB) to serve as a target for the discovery of new AeHKT inhibitors and optimization of 1,2,4-oxadiazole derivatives. We have further performed a series of metadynamics (Meta-MD) simulations to compute the multidimensional free energy surface (FES) for the binding process between the two HKT enzymes (AeHKT, AgHKT) and two inhibitors: 4OB, previously cocrystallized in complex with AgHKT, and a canonical representative of the 1,2,4-oxadiazole derivatives, sodium 4-(3-phenyl-1,2,4-oxadiazol-5-yl)­butanoate (OXA) . Since 4OB is the sole HKT inhibitor for which the enzyme-inhibitor complex crystallographic data is available, it serves as the gold standard for validation of new inhibitors via structure-based approaches.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The second generation of sodium 4-[3-aryl-1,2,4-oxadiazol-5-yl] propanoates has also been synthesized and examined. 67 According to QSAR analysis, shortening the chain has been proved to be beneficial for larvicidal activity. As an example, compound 27 displayed an IC 50 value of 42 ± 1 μM, indicating greater potency than the first-generation inhibitor 25 .…”
Section: 24-oxadiazole Derivatives With Pesticidal Activitymentioning
confidence: 99%